Customer Satisfaction Based on Product Variants and Prices (Case Study on Indomaret Cibening Purwakarta) - Rivan Nur Rahman; Duki Adam (Trescode Green Organization, 2024)
This study aims to analyze the Influence of Product Variants and Prices on Customer Satisfaction in Indomaret Cibening Purwakarta. This study aims to analyze the Influence of Product Variants and Prices on Customer Satisfaction in Indomaret Cibening Purwakarta. The problems that exist in the retail business with the current condition that the retail market is dynamic, especially regarding price competition and product variants, careful analysis of the influence of customer satisfaction, pricing, and product variants is the main key. The current marketing conditions at Indomaret Cibening are still monotonous, using discount promos, and advertisements made from central Indomaret are problems related to efforts to create customer satisfaction experienced by Indomaret. The source of data in this study was obtained from a questionnaire (primary) distributed to the respondents. The population of this study is customers who visit Indomaret Cibening Purwakarta. The research sample was 161 people. The analytical test tool used is SmartPLS 4.0. The results of this study show that Customer Satisfaction has a significant positive influence with an R-Square value of 0.905.